PROTECTION OF INDONESIA’S PERSONAL DATA AFTER RATIFICATION OF PERSONAL DATA PROTECTION ACT - Siti Yuniarti (Faculty of Law-Universitas Bandar Lampung, 2022)
The protection of Indonesia's personal data entered a new chapter with the signing of the Personal Data Protection Bill by the President on October 17, 2022. The presence of the Personal Data Protection Law (UU PDP) is a lex specialist of Indonesian personal data protection regulations. This study analyzes how the form of protection of Indonesian personal data after the enactment of the PDP Law by using components in the personal data protection ecosystem as parameters, namely data subjects, data controllers and data processors, data protection officers and personal data protection supervisory agencies. Using normative legal research methods, this study found that the regulation of the 4 components has been accommodated in principle in the PDP Law. The balance between the protection of individuals on the one hand and the public interest on the other is tried to be accommodated in the principles behind the PDP Law and the reduction of the implementation of some norms. The composition of the norms shows that the processing of personal data, especially the obligations of the data controller, is the focus of regulation. The role of a data protection officer to ensure regulatory compliance is complemented by a risk mitigation function. The existence of data protection as service is also accommodated in the PDP Law. The supervisory agency is given a series of authorities with detailed details of investigative authority. The PDP Law as a compact regulation requires various implementing regulations, including provisions issued by institutions and sectoral regulations. The support of understanding and strengthening of all parties in the personal data protection ecosystem absolutely needs to be carried out immediately as an effort to realize compliance by minimizing protection failures and unauthorized processing as a preventive measure. Preventive measures should be used as a key option in the data protection regime. Therefore, discussions regarding the protection of personal data continue to move dynamically following emerging legal and social developments.